Calidad percibida por las asociaciones del sector textil de la ciudad de Loja en relación a los procesos de acompañamiento e inserción del Instituto de Economía Popular y Solidaria, periodo 2017” - Benites Acaro, Katherine Anabel (2018)
The present research work entitled: "Perceived Quality by the Associations of the Textile Sector of the city of Loja in relation to the Processes of Accompaniment and Insertion of the Institute of Popular and Solidarity Economy, period 2017", has as main objective to determine the level of quality perceived by the clusters of the textile sector of the city of Loja, based on a review of literature given in three instances: the first, refers to the legal regulations, established in articles of the Constitution of the Republic of Ecuador, Codes, Laws Organic and the National Development Plan 2017-2021, which guarantee the existence of quality in public services; and, secondly, the conceptual framework that contains theoretical foundations that make it possible to achieve the objectives and, finally, the referential framework, who gives a detail of the institution involved. Methodologically, it was based on a mixed approach, since quantitative data obtained from the application of 191 surveys was required to determine expectations and perceptions of textile partners with respect to the services received, supplemented by the results of the interviews carried out with departmental heads of the Institute and some presidents of the associations. In this way, the main results were obtained that the perceptions of those involved in the textile sector are lower than their expectations, which generates a gap of -0.80, reflecting poor quality in the services received by the textile associates of the city. of Loja in the year 2017 by the Institute of Popular and Solidarity Economy. For the development of the discussion and in the later to establish conclusions and recommendations of the present investigation, the legal regulations and the respective theoretical foundations established in the literature review were taken into consideration.